Complement and Chlamydia psittaci: Non-Myeloid-Derived C3 Predominantly Induces Protective Adaptive Immune Responses in Mouse Lung Infection - Kohn, Martin; Lanfermann, Christian; Laudeley, Robert; Glage, Silke; Rheinheimer, Claudia; Klos, Andreas (Frontiers in Immunology, 2021)
Recent advances in complement research have revolutionized our understanding of its role in immune responses. The immunomodulatory features of complement in infections by intracellular pathogens, e.g. viruses, are attracting increasing attention. Thereby, local production and activation of complement by myeloid-derived cells seem to be crucial. We could recently show that C3, a key player of the complement cascade, is required for effective defense against the intracellular bacterium Chlamydia psittaci. Avian zoonotic strains of this pathogen cause life-threatening pneumonia with systemic spread in humans; closely related non-avian strains are responsible for less severe diseases of domestic animals with economic loss. To clarify how far myeloid- and non-myeloid cell-derived complement contributes to immune response and resulting protection against C. psittaci, adoptive bone marrow transfer experiments focusing on C3 were combined with challenge experiments using a non-avian (BSL 2) strain of this intracellular bacterium. Surprisingly, our data prove that for C. psittaci induced pneumonia in mice, non-myeloid-derived, circulating/systemic C3 has a leading role in protection, in particular on the development of pathogen-specific T- and B- cell responses. In contrast, myeloid-derived and most likely locally produced C3 plays only a minor, mainly fine-tuning role. The work we present here, describes authentic, although less pronounced, antigen directed immune responses.